2016
DOI: 10.1063/1.4959090
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigations of nano-Schottky contacts

Abstract: Formation of metal-semiconductor (M-S) contacts at sub-20 nanometer range is a key requirement for down-scaling of semiconductor devices. However, electrical measurements of M-S contacts at this scale have exhibited dramatic change in the current-voltage (I-V) characteristics compared to that of conventional (or planar) Schottky contacts. This change is actually attributed to the limited metal contact region where the transferred charge from the semiconductor into the metal is confined to a small surface area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…10 ). The enhanced current in the reverse bias regime is in agreement with the behavior of nanoscale Schottky junctions, which usually show smaller current under forward bias and inverse rectification under reverse bias 33 .
Fig.
…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…10 ). The enhanced current in the reverse bias regime is in agreement with the behavior of nanoscale Schottky junctions, which usually show smaller current under forward bias and inverse rectification under reverse bias 33 .
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…Interestingly, in a nanoscale Schottky contact, the depletion width is reduced with decreasing the tip radius r . This effect leads to an increased tunneling probability at the interface in the reverse low-bias regime and the expectation of a higher current for smaller tip radius, which is in contrast with the observed higher absolute current in the case of Au-coated probes ( r < 35 nm radius of curvature), with respect to the PtIt-coated probes ( r < 25 nm radius of curvature) 33 . However, the tip radius of the curvature does not describe the actual probe/sample contact area during measurement.…”
Section: Resultsmentioning
confidence: 67%
“…Thus, the smaller energy band width facilitates higher tunneling probability for electrons from the tip into n-Si substrate, leading to higher magnitude of the reverse tunneling current, for the positive sweep voltage at the substrate. This basic nano-Schottky model is detailed elsewhere 28,34 . For further understanding of the electric field enhancement at the nano-tip/Semiconductor interface, models for two probes with 15 nm and 5 µm radii are constructed using physics-based TCAD simulation to map the interface electric field.…”
Section: Resultsmentioning
confidence: 99%
“…The conductive-probe atomic force microscopy (C-AFM) has been used as a powerful tool to investigate the photodetection at the nano-scale MS junctions 2830 . The main advantage of C-AFM electrical measurement is its ability to gather local conductivity information 3133 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the tunneling current is a direct function of the electric eld at the nano metal/Si junction, and the I-V behavior is reproducible when using the same Au AFM probe on a clean n-Si surface. 12,33 Therefore, the drop in the tunneling current at the Au NP/n-Si interface at subsequent voltage sweeps, as shown Fig. 3, is a result of the reduction of the interface electric eld due to the charge screening effect from the Au-NP.…”
Section: Resultsmentioning
confidence: 97%